Rethinking Equality in the Global Society - Dorsey D. Ellis Jr.; John Bowen; Clark D. Cunningham; Pauline T. Kim; John J. Donohue; B.P. Jeevan Reddy; Sunita Parikh; Linda Krieger; Aaron Porter; Pansy Tlakula; Garrett Duncan; Joshua Aronson; et al. (Washington University Law Quarterly, 1997)
The future of affirmative action, especially in the area of American higher education, has been called into question by the 1996 decision of the U.S. Court of Appeals for the Fifth Circuit in Hopwood v. State of Texas, requiring race-blind admission to state universities in Texas, and the passage of Proposition 209 in California. The seemingly endless American debate on this issue almost entirely has ignored the fact that other countries faced with comparable problems of remedying the effects of past discrimination have developed programs and acquired experience from which Americans might learn. Further, the legal debate has not been adequately informed by the social science disciplines. This conference was intended to expand discussion at a critical moment by introducing these missing perspectives.
Keywords: Affirmative action programs